Métodos de análisis y diseño para la resolución de problemas de estabilidad de taludes y excavaciones mediante técnicas de soil nailing (2018)
This article presents the results of a study of the main aspects that affect the behavior of soil nailing structures (spiked soil), the interaction between the main elements of the system, their behavior variables and their contribution to global stability of the system. Four types of soil in the city of Bogotá were analyzed: hard clays, soft clays, dense sands and loose sands (this classification applies to the soils studied in the present investigation). For the characterization of the materials, the results of the field and laboratory tests of the soil studies for phases I and II of the metro. Models were made in the limit equilibrium programs SNAP-2 and Slide, and in the finite element program RS2.